Evolution of transcript modification by N6-methyladenosine in primates - Ma, Lijia; Zhao, Boxuan; Chen, Kai; Thomas, Amber; Tuteja, Jigyasa H.; He, Xin; He, Chuan; White, Kevin P. (Genome Research, 2017)
Phenotypic differences within populations and between closely related species are often driven by variation and evolution of gene expression. However, most analyses have focused on the effects of genomic variation at cis-regulatory elements such as promoters and enhancers that control transcriptional activity, and little is understood about the influence of post-transcriptional processes on transcript evolution. Post-transcriptional modification of RNA by N6-methyladenosine (m6A) has been shown to be widespread throughout the transcriptome, and this reversible mark can affect transcript stability and translation dynamics. Here we analyze m6A mRNA modifications in lymphoblastoid cell lines (LCLs) from human, chimpanzee and rhesus, and we identify patterns of m6A evolution among species. We find that m6A evolution occurs in parallel with evolution of consensus RNA sequence motifs known to be associated with the enzymatic complexes that regulate m6A dynamics, and expression evolution of m6A-modified genes occurs in parallel with m6A evolution.